Using Scenedesmus sp. for the Phycoremediation of Tannery Wastewater - Ballén Segura, Miguel; Hernández Rodríguez, Luisa; Parra Ospina, David; Vega Bolaños, Asly; Pérez, Karen (TECCIENCIA, 2016)
Wastewater from the leather tannery industry contains high concentrations of heavy metals, especially chromium, as well as high values of inorganic nutrients and organic matter which, if not treated prior to discharge, may alter the quality of surface water bodies. As an alternative treatment to these industrial effluents, we propose the use of microalgae, due to their ability to remove contaminants. This study evaluates the growth of the microalga Scenedesmus sp. in three different dilutions of wastewater (20%, 50%, and 100%) at a tannery in Bogotá, Colombia, for a period of 15 days. We assess the removal of hexavalent chromium, nutrients (nitrites, nitrates, phosphates and sulfates), and Biochemical Oxygen Dilution (BOD). Results indicate a growth of Scenedesmus proportional to the dilution of the effluent, with greater biomass in undiluted wastewater. This biomass achieved the removal of Cr+6 (>98%), nitrates (>90%) and phosphates (>99%), and BOD (>88%) which can be attributed to a shared microalgae-bacteria effect. Thus, we conclude that the microalgae Scenedesmus sp. Used the waste effluent as a growth substrate, improving its effect during a phycoremediation process.